ANALYSIS OF STRATEGIES TO IMPROVE EMPLOYEE PERFORMANCE TO ACHIEVE PERFORMANCE BASED CAPITATION (PBC) AT THE CICANGKANGGIRANG HEALTH CENTRE, WEST BANDUNG REGENCY - Nurhaeni Sikki; Wahyudin Wahyudin; Mustoha Mustoha; Badi Munawir; Suriansyah Suriansyah (LPPM Universitas Bina Bangsa, 2025)
This study aims to analyze strategies for improving employee performance to achieve Performance Based Capitation (PBC) at the Cicangkanggirang Health Centre, West Bandung Regency. As a primary health care provider, Puskesmas plays a critical role in enhancing community health outcomes through basic health services. The implementation of PBC as a performance-based incentive system requires improvements in employee productivity and service quality. Using a qualitative approach and SWOT analysis, this study identifies key internal and external factors affecting PBC achievement. The findings highlight challenges related to human resource limitations, suboptimal performance, and inadequate facilities, alongside opportunities from government support and digital innovation. Strategic recommendations include sustainable human resource development, digital service innovation, employee motivation enhancement, and optimized resource utilization to support improved performance and PBC outcomes.